Novosti . Novosti . News . Новости - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Deferment of the payment of Russian debt; amendment of the defense law; approval of a single wage scale for employees of the public sector; conference at the U.S. Chamber of Commerce. Contributors: Osokin, Mikhail Glebovich (Anchor) Series description: A program of Channel One, broadcasted since February 10, 1986. It surveys the information from the passed part of the day, including sport news and weather forecast. Broadcasted several times a day with the interval 2-3 hours. Until October 14, 1990, the program was called "News." Before 1991 the program was produced by the Studio of information programs of the Central Television, and from 1991 - by the newly crated Information Tevevision Agency. In 1986-1994 the program's timing was from 6 to 21 minutes. From October 1991, evening broadcasts were anchored by Tatiana Komarova, Sergei Medvedev, Irina Mishina, and Pavel Kasparov, and the night broadcasts were anchored by Mikhail Osokin and Dmitrii Kiselev. From February 1992 to September 1993 Sergei Dorenko was the anchorman of the evening issue instead of Pavel Kasparov. Отсрочка уплаты российских долгов, внесение поправок в закон об обороне, одобрение единой тарифной сетки для работников бюджетной отрасли, конференция в торговой палате США. Создатели: Осокин, Михаил Глебович (Ведущий/Ведущая) Описание серии: Программа Первого канала, выходящая в эфир с 10 февраля 1986 года по сей день. Представляет собой обзор информации за прошедшую часть дня, включая новости спорта и прогноз погоды. Выходит в эфир несколько раз в день с интервалом 2-3 часа. До 1991 года программа выпускалась Студией информационных программ Центрального Телевидения, с 1991 года - вновь созданным Информационным Телевизионным Агенством. В 1986-1994 годах хронометраж программы составлял от 6 до 21 минуты. Ведущими вечерних выпусков с октября 1991 года стали Татьяна Комарова, Сергей Медведев, Ирина Мишина, Павел Каспаров, ведущими ночных выпусков — Михаил Осокин и Дмитрий Киселёв. С февраля 1992 года по сентябрь 1993 года ведущим вечернего выпуска программы стал Сергей Доренко вместо Павла Каспарова.